Estimation of the accuracy and informativeness of measuring intraocular pressure in patients with their contact lenses on by transpalpebral scleral tonometry - N. Yu. Kushnarevich; E. N. Iomdina; A. M. Bessmertny; M. N. Kuzin (Российский офтальмологический журнал)
Purpose: to compare the tonometry results obtained by transpalpebral scleral tonometry and pneumotonometry for patients with their contact lenses on. Material and methods. Intraocular pressure (IOP) was measured in 30 (60 eyes) patients with various refraction errors including 5 patients (10 eyes) aged 11–63 (45.0 ± 21.0) years with hyperopia of +1.75 to +9.0 D (+4.4 ± 2.6 D) and 25 patients (50 eyes) aged 12–57 (26.4 ± 13.5) years with myopia of -0.5 to -11.25 D (-4.4 ± 2.4 D). In most of cases patients used soft daily disposable contact lenses (spherical or multifocal). IOP was determined in both eyes of each patient using 1) transpalpebral scleral tonometry (EASYTON tonometer), and 2) corneal pneumotonometry. IOP was first measured when the patient was without their contact lenses, by both methods consecutively. 20 minutes after putting the lenses on, IOP was measured once again. Each measurement was taken three times and the average IOP value was determined. The data were analyzed using parametric statistics: the mean value and the standard deviation (M ± SD) of each parameter were calculated. Results. On average, patients without contact lenses showed transpalpebral IOP (IOPtr) of 16.3 ± 2.9 mmHg in the right eye (OD) and 16.6 ± 3.2 mmHg in the left eye (OS) and pneumotonometry IOP (IOPpn) of 16.0 ± 3.8 in OD and 15.6 ± 3.3 mmHg in OS. When the lenses were put on, the values of IOPtr stayed practically the same: 16.0 ± 3.9 mmHg in OD and 16.7 ± 3.1 mmHg in OS. IOPpn also changed insignificantly: 15.7 ± 2.9 mmHg in OD and 15.5 ± 2.8 mmHg in OS, but individual IOPpn data scattered more when the lenses were put on. IOPtr of hyperopic patients both with the lenses (19.5 ± 3.9 mmHg in OD and 19.7 ± 3.3 mmHg in OS) and without them (19.3 ± 2.8 mmHg in OD and 19.6 ± 3.1 mmHg in OS) was higher than IOPpn both with the lenses (14.0 ± 1.8 mmHg in OD and 14.2 ± 1.7 mmHg in OS) and without them (13.5 ± 2.7 mmHg in OD and 13.2 ± 1.6 mmHg in OS). A higher IOPtp in the hyperopic group seems more plausible because most patients in this group were significantly older than in myopic group. In hyperopic patients, IOPpn level in lenses tended to be higher than without them, while IOPtr was the same in either case. It may be due to the fact that contact lenses for high hyperopia are rather thick, which affects the air impact on the cornea during pneutonometry. In the myopic group the difference between IOPtr (15.2 ± 3.5 mmHg in OD and 16.0 ± 2.7 mmHg in OS) and IOPpn (16.1 ± 2.9 mmHg in OD and 15.9 ± 3.0 mmHg in OS) in lenses and IOPtr (15.7 ± 2.6 mmHg in OD and 15.9 ± 2.9 mmHg in OS) and IOPpn (16.6 ± 3.8 mmHg in OD and 16.1 ± 3.4 mmHg in OS) without them was insignificant. Conclusion. Transpalpebral scleral tonometry using EASYTON is an adequate method to measure IOP of patients with contact lenses on and can be the method of choice in a some of clinical cases, since its results and their repeatability are not affected by factors associated with the presence of a contact lens.